Educative Spaces Full of Potential: Kairos Moments and Quantum Leaps - Evans, Nelia; Hill, Cher (The Canadian Journal of Action Research, 2024)
In this paper I share stories about beautifully complex and novel pathways for learners on the margins within my under-resourced Grade 2 community school classroom. I challenged practices of schooling that produced static understanding of children, and ones in which they were compared to the average, by embracing kairos moments. Kairos moments are distinct spaces full of potential that ebb and flow in unexpected ways and may lead to unanticipated outcomes. Inspired by new materialist scholarship, I worked at the intersection of theory and practice to go beyond common inclusive and self-regulatory educational strategies, to focus on the complex relationships involving children and their material contexts. Through the story of the magic pencil and the story of the invisible string, I illuminate the infinite potential within pedagogical spaces.